Image Encryption Based on Complicated Chaotic (Journal of Fiber Bioengineering and Informatics, 2015)
In order to improve the security of secret image transmission, using the property of the chaotic sequence\rin the encryption algorithm, a block image encryption scheme based on Logistic and Henon composite\rchaotic system is presented. The image encryption algorithm from two aspects that the pixel grayscale\rvalue and pixel position through two different chaotic sequences transform of the Logistic and Henon. At\rfirst, Logistic chaotic sequence is applied to the scrambling operation on the pixel position matrix. Then\rthe pixel values of blocked images are scrambled based on Henon chaotic sequence. The experiments\rshow that the algorithm has good encryption effect, and has better robustness to crop or noise attack.\rThe cross correlation of encrypted image are decreased and the transport security is improved, the result\rshows that the project is effective.